Routine Early 68Ga-DOTATATE Positron Emission Tomography Has Low Yield After Resection of Appendiceal Neuroendocrine Neoplasms. Issue 7 (August 2020) - Chan, David L.; Hoang, Jeremy; Roach, Paul J.; Arena, Jennifer; Bailey, Dale L.; Nevell, David; Pavlakis, Nick; Engel, Alexander; Bernard, Elizabeth J.
Abstract : Objectives: Appendiceal neuroendocrine neoplasms (appNEN) generally carry a low recurrence risk. 68 Ga-DOTATATE positron emission tomography (DOTA PET) is increasingly used as it is more sensitive than cross-sectional imaging. We hypothesize that early DOTA PET is unlikely to detect recurrent disease in patients with low-risk resected appNEN because of the delayed pattern of recurrence. Methods: Retrospective study (dual review) of patients undergoing DOTA PET 0 to 18 months after resected appNEN. The primary outcome was the proportion of scans demonstrating residual disease. Results: Forty-one patients were included (median age, 29 years; 63% female), most with small, low-grade appNEN. No scans (0%) showed residual/distant disease. Eight (20%) of 41 scans showed indeterminate findings requiring follow-up. Five (12%) scans were recommended for follow-up with modalities other than DOTA PET (vertebra, 3; thyroid; bone, 1 each). Three (7%) were recommended for follow-up with DOTA PET (all with indeterminate abdominal uptake). These 3 patients had no recurrent disease on follow-up. Conclusions: The 68 Ga-DOTATATE PET is of no value when performed in the first 18 months after resected appNEN. Although 20% of scans showed indeterminate findings, more than half did not require repeat DOTA PET. Despite advantages over cross-sectional imaging, DOTA PET is not recommended in staging after completely resected appNEN. Abstract : Supplemental digital content is available in the text.